The Rat Thoracic Ultrasound protocol: scanning technique and normal findings - Piskovská, Anna; Kraszewska, Katarzyna; Hauptman, Karel; Jekl, Vladimír (Frontiers in Veterinary Science, 2024)
Respiratory diseases (especially pneumonia) are very common disorders in pet rats. The suspected diagnosis is mostly based on the clinical signs, thoracic auscultation, and thoracic radiography. However, auscultation is insensitive in determining the severity of the disease, and radiographs are often unremarkable. Non-cardiac thoracic ultrasonography is increasingly used in veterinary medicine; however, it has not been described in detail in rats. Thoracic ultrasonic examination was conducted on 400 client-owned conscious pet rats. The rats were examined in the period from June 2023 to August 2023 in two veterinary clinics. Due to the small size of the animal, different anatomical considerations, and different evaluation protocols, as well as to meet the optimal outcome of detailed thoracic ultrasound, a standard methodological protocol was developed, and the name RATTUS (Rat Thoracic Ultrasound) was proposed. Typical signs of normal RATTUS were described (bat sign, lung sliding, A-lines, abdominal curtain sign, ski jump sign, lung pulse, seashore sign in M-mode, and bamboo sign). The new evaluation of lung inflation symmetry by substernal access was also described. The methodical approach presented and the normal findings description are proposed to be used for a standard/routine thoracic ultrasound examination in pet rats.